THE WORKS OF GOTTHOLD EPHRAIM LESSING PLAYS AN IMPORTANT ROLE IN THE STUDY OF THE ESSENCE OF HUMANITY - Mamatova Anora Iminovna (Scholar Express Journal, 2022)
This article discusses the role of methodological tools in the works of Gotthold Ephraim Lessing. Thus, in thinking and acting like true representatives of the Enlightenment, the two eventually behave like ordinary people and so bear witness to Lessing’s concept of humanity. He made an excellent analysis of the possibilities of image creation in oral and fine arts. In his opinion, literature not only calms with beauty, but also excites the mind. At the same time, it is well covered in the article that the methodological tools in the translation of his works have played an important role in revealing the true essence of the work.
Keywords: Representative; Eventually Behave; Directed Against; Greed For Wealth